A novel security mechanism using AES cryptography approach in cloud computing. (10th November 2020) - B, Muthulakshmi; M, Venkatesulu
Summary: For a smart cloud computing system, security and privacy are the required factors. In recent days, the evolvement of cloud technology is immense, according to which several cloud service providers (CSPs) evolved. Each CSP has its infrastructure with its security policies. Even though still the security in cloud computing is an existing challenge, it is more important to maintain the trustiness of cloud environment among the cloud users. On this motto, we propose a novel tailored—advanced encryption standard (AES) Cryptographic Algorithm (TCA). AES is one of the popular cryptography algorithms. We indulged in increasing the performance of this algorithm by minimizing the time taken for the cryptography process. Here, the cryptography is processed with AES algorithm. In order to improve the efficiency of AES, a concept of a chunk file system is introduced. The input file is chunked into multiple which facilitates quick and effective encryption. To prove the efficiency of our proposed system, a comparison work is carried out with the existing algorithms lightweight keyword searchable encryption (LFSE) and cloud key management system (CKMS). The comparison work is based on the aspect of time taken during key generation, encryption and decryption. The obtained result is plotted, and comparison output clearly states our TCA's excellence in the aspect of efficiency compared to others. Abstract : To improve the efficiency in our proposed mechanism, a comparison work is accomplished with the existing algorithms lightweight keyword searchable encryption (LFSE) and cloud key management system (CKMS). In our proposed experimental set up, the parameter is used: (a) number of attributes and key generation time, (b) number of attributes and encryption time, (c) number of attributes and decryption time. The obtained result is plotted, and comparison output clearly states our TCA's excellence in the aspect of efficiency compared to others.